Global order and its enemies - Moszyński, Michał (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: A series of crises have demonstrated the low resilience of the global economy to shocks and triggered a discussion about the possible end of globalisation understood as the unrestrained growth of mutual trade and business ties on a global scale. The emerging tendencies to shorten supply chains and block trade as well as calls for an active and strategic trade policy are contributing to the decay of the liberal global order built after World War II. The potential disintegration of the world economy into antagonised blocs and the conflict between the Western model of liberal democracy and autocratic regimes should be considered particularly dangerous. The above phenomena deserve the utmost attention, and the desire to understand them has provided inspiration for taking up this topic. Aim: This study aims to define and interpret the concept of global order in both economic and political dimensions. In this context, two interrelated questions are addressed. The first one is about the character of the global order after World War II and the second one concerns the causes and consequences of its decay. Results: The emerging disintegrative tendencies in the global economy and the anarchisation of international economic relations constitute a negative-sum game. Globalisation has allowed most countries in the world to achieve significant gains in wealth. The benefits that it provides to consumers are too great to be consciously abandoned in favour of an autarkic economic model. Capitalism seems to be able to operate under very different political regimes, hence — with all the differences between political models at the national level — it creates an effective platform for cooperation on the global stage. Nevertheless, the end of the “peace dividend” indicates that effectively preventing the danger of armed conflict by means of economic and military deterrence will be an important part of the future world order.